Safeguarding forest ecosystems: harnessing IoT for fire detection - Iman Atighi; Zhi Zhou (Big Data and Computing Visions)
Forest fires represent a significant threat to natural ecosystems and human lives, necessitating early detection and rapid response for effective mitigation. In recent years, the Internet of Things (IoT) has emerged as a promising technology for forest fire detection. IoT-based solutions leverage Wireless Sensor Networks (WSNs), which consist of sensor nodes equipped with various sensors, data processing capabilities, and wireless communication, all powered by batteries. Energy efficiency is a critical consideration for WSNs, as they lack the luxury of periodic recharging. This paper explores the utilization of IoT-enabled WSNs in forest fire detection, with a specific focus on the sensor nodes' ability to monitor environmental parameters such as temperature, pressure, and humidity, as well as chemical indicators including Carbon Monoxide, Carbon Dioxide, and Nitrogen Dioxide. The self-healing and self-organizing characteristics of IoT sensor networks enhance their reliability and robustness in remote forested areas. ZigBee, based on IEEE 802.15.4, is a wireless technology that has gained prominence due to its low-cost, battery-powered applications and suitability for low data rates and short-range communications. This paper highlights the advancements, challenges, and potential applications of IoT-enabled WSNs for forest fire detection, underscoring the expanding possibilities enabled by the rapid development of the IoT. It emphasizes the growing research interest in IoT sensor networks and their potential deployment in various domains. The insights provided aim to contribute to ongoing efforts in developing efficient forest fire detection systems, ultimately enhancing the safety and preservation of our natural environment.